DEVELOPMENT OF A TRADITIONAL GAME MODEL TO IMPROVE THE QUALITY OF LIFE OF STUDENTS WITH SPECIAL NEEDS IN SPECIAL SCHOOLS - Armanjaya, Satria; Rachman, Fadlu; Alvindo, Dodi (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2025)
This study aims to develop a traditional game model adapted to the characteristics of students with special needs to improve their quality of life in Special Needs Schools. The research method used is Research and Development by adapting the Borg & Gall model that has been modified simply. The research subjects involved students from various levels of education in special needs schools. Research data was obtained through observation, interviews, questionnaires, as well as limited and extensive trials of the developed traditional game models. Data analysis was carried out descriptively qualitatively and quantitatively to assess aspects of feasibility, implementation, and the impact of the game on students' quality of life. The results of expert validation of the four game models showed a maximum achievement of 100%. This confirms that the four game models are considered very suitable for application to students with special needs. Meanwhile, based on the World Health Organization Quality of Life questionnaire which consists of 26 questions and covers four domains of quality of life assessment. The physical domain is 40% in the good category, 60% in the sufficient category. The psychological domain, 40% is in the very good category, 33% in the good category, 27% in the sufficient category. In the social domain, 27% were in the excellent category, 46% in the good category, and 27% in the fair category. In the environmental domain, 33% were in the excellent category, 34% in the good category, and 33% in the fair category. Overall, the findings of this study demonstrate that the traditional game model is effective in supporting the improvement of the quality of life of students with special needs in special needs schools.